Comparative characteristics of flexible splints for transport immobilization presented on the market of the Republic of Belarus - A. L. Mikhailovskiy; F. I. Satsuk (Military Medicine, 2026)
The article presents a comparative assessment of the technical and operational characteristics of flexible immobilization splints available on the market of the Republic of Belarus. The relevance of using these tools at the prehospital stage in modern armed conflicts is substantiated. The results of an X-ray examination confirming the X-ray negativity of all tested samplesarepresented. It is concluded that it is expedient to prioritize purchases of local products (OJSC «Svetlogorsk-Khimvolokno») within the framework of the import substitution program.